2017
DOI: 10.1007/s10511-017-9500-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Gamma-Ray Burst Sources

Abstract: The spatial distribution of sources of gamma-ray bursts (GRB) with known red shifts is analyzed by the conditional density and pairwise distance methods. The sample of GRB is based on data from the Swift mission and contains fluxes, coordinates, and red shifts for 384 GRB sources. Selection effects that distort the true source distribution are taken into account by comparing the observed distribution with fractal and uniform model catalogs. The Malmqvist effect is modeled using an approximation for the visible… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The works by Nabokov and Baryshev [8], Lovyagin [23], Shirokov et al [30], Park et al [31] emphasize the importance of the analysis of the LSSU for the development of modern cosmology, which has become an increasingly important task in the 21st century. The spatial distribution of galaxies reflects both the initial conditions in the early Universe and the evolution of primordial density perturbations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The works by Nabokov and Baryshev [8], Lovyagin [23], Shirokov et al [30], Park et al [31] emphasize the importance of the analysis of the LSSU for the development of modern cosmology, which has become an increasingly important task in the 21st century. The spatial distribution of galaxies reflects both the initial conditions in the early Universe and the evolution of primordial density perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…Super-large fractal-like structures with scales of more than 100 Mpc reveal themselves both in the spatial distribution of galaxies in the local Universe at redshifts of z 0.1 and in the quasars and gamma-ray bursts distributions at redshifts of z ∼ 2 [3,25,30,[32][33][34][35]. The analysis of fractal properties [3,32,36] can be used to describe the properties of the large-scale distribution of matter [25,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditional density analysis of main galaxy samples was developed in [30], [15], [88]. Pairwise method was developed in [64,75].…”
Section: Testing Cosmological Principle By Grb Observationsmentioning
confidence: 99%
“…Balázs et al (2015Balázs et al ( , 2018 found an over-density of GRBs in the redshift range of 0.78 < z < 0.86 (comoving distance of 2 770 Mpc), which forms a ring-like shape displayed by 9 GRBs with a diameter of 1 720 Mpc. Other recent works which study the spatial distribution of GRBs with known redshift were done by Raikov et al (2010); Shirokov et al (2017).…”
Section: Introductionmentioning
confidence: 99%